3,3’-Di(5,7-dibromoindol-3-il)-indolin-2-on: Sintesis dan Uji Sitotoksik terhadap Sel Kanker Kolon WiDr - KAMILIA MUSTIKASARI; MARDI SANTOSO (Fakultas Farmasi Universitas Pancasila, 2013)
Colon cancer is one of the causes of death in the world of concern, because until now there has not been found specific drug for its treatment. Therefore, the study aimed to synthesize compounds that have the potential as a novel anticancer compound derivative such as 3,3’-di (indol-3-yl) indolin-2-one is required. Synthesis was done by reacting 5,7-dibromoindole and isatin in methanol with an acid catalyst to produce 3,3’-di (5,7-dibromoindol-3-yl)-indolin-2-one compound with a yield of 48%. 3,3 ‘-di (5,7-dibromoindol-3-yl)-indolin-2-one is cytotoxic against colon cancer cell line WiDr with IC50 of 6.64 μM.